2018
DOI: 10.1177/1938965518797075
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Aspects of the Chameleon Effect and Hospitality: The Link Between Mimicry, Its Impact, and Duration

Abstract: In an experiment conducted in natural settings (in a restaurant), we explore the uninvestigated link between mimicry, its impact on hospitality, and the time during which the mimicry takes place. Under particular experimental conditions, the waitress either did not verbally mimic the customer, mimicked the customer only at the initial stage of the interaction, only at the final stage of the interaction, or at both the initial and the final stage of the interaction. The tip left by the customer and its amount w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Firstly, the temporal aspects of mimicry have recently been reported, answering the question of how long one should mimic to be granted benefits. It was shown that mimicry is beneficial even after a short period (5 minutes; and that mimicry outcomes were the highest when mimicry was applied twice (at the beginning and at the end of an interaction; [ 71 , 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the temporal aspects of mimicry have recently been reported, answering the question of how long one should mimic to be granted benefits. It was shown that mimicry is beneficial even after a short period (5 minutes; and that mimicry outcomes were the highest when mimicry was applied twice (at the beginning and at the end of an interaction; [ 71 , 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, waiters at a restaurant were instructed to repeat customers' orders when taking them (vs. making their understanding clear without verbal mimicry). Those instructed to repeat the orders verbatim received higher tips (Kulesza et al, 2019; Van Baaren et al, 2003). Negotiators who mimicked the verbal expressions of their counterparts elicited more trust and achieved better outcomes than those who did not, but only when the mimicry occurred early (vs. late) in the negotiation (Swaab et al, 2011).…”
Section: The Components Of Listening and Their Constituentsmentioning
confidence: 99%
“…The experiment showed that mimicry is not only beneficial (replicating laboratory studies), but even a short period (5 min) of mimicry boosts quality judgments showing the impact of mimicry on service quality evaluations. Kulesza and colleagues ( Kulesza et al, 2019 ) extended this line of research to a restaurant setting, in which a waitress mimicked customers. Finally, in the control condition, no mimicry took place.…”
Section: Introductionmentioning
confidence: 99%
“…Mimicry in both laboratory and natural settings creates trust ( Maddux et al, 2008 ; Swaab et al, 2011 ) and rapport ( Muir et al, 2020 ), it also influences purchasing decisions ( Tanner et al, 2008 ; Jacob et al, 2011 ; Stel et al, 2011a ; Kulesza et al, 2014b , 2017 , 2019 , 2022b ; Christie and Chen, 2018 ) by eliciting susceptibility to the persuasiveness of the mimicker ( Van Swol, 2003 ; Drury and Van Swol, 2005 ). On this grounds, it may be assumed that research on mimicry and its spillover potential has focused mainly on products, and only partially considered the crucial aspect of spreading the benefits of mimicry to the entire company/organization.…”
Section: Introductionmentioning
confidence: 99%